2021
DOI: 10.1128/mbio.03671-20
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting Cellular Function and Distribution of β-Glucosidases in Trichoderma reesei

Abstract: Trichoderma reesei has 11 putative β-glucosidases in its genome, playing key parts in the induction and production of cellulase. Nevertheless, the reason why the T. reesei genome encodes so many β-glucosidases and the distinct role each β-glucosidase plays in cellulase production remain unknown. In the present study, the cellular function and distribution of 10 known β-glucosidases (CEL3B, CEL3E, CEL3F, CEL3H, CEL3J, CEL1A, CEL3C, CEL1B, CEL3G, and CEL3D) were explored in T. reesei, leaving out BGL1 (CEL3A), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 70 publications
2
19
0
Order By: Relevance
“…This data was consistent with the reported finding that cel1b was highly induced in T. reesei cultivated on cellulose or sophorose together with cel1a [ 31 ], whose transcriptional levels were only second to the major extracellular β-glucosidase CEL3A [ 22 ], demonstrating that cel1b might be actively involved in the cellulase biosynthesis in T. reesei . Our previous study has shown that cel1b overexpression using an inducible cbh1 promoter led to a dramatic decrease in cellulase production on cellulose as observed in T. reesei Rcel1B, while the overexpression of other β-glucosidases did not [ 22 ]. We wondered if the decrease on cellulase production was due to that the promoter cbh1 was too strong, which was considered as the strongest promoter in T. reesei on cellulose [ 40 , 41 ].…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…This data was consistent with the reported finding that cel1b was highly induced in T. reesei cultivated on cellulose or sophorose together with cel1a [ 31 ], whose transcriptional levels were only second to the major extracellular β-glucosidase CEL3A [ 22 ], demonstrating that cel1b might be actively involved in the cellulase biosynthesis in T. reesei . Our previous study has shown that cel1b overexpression using an inducible cbh1 promoter led to a dramatic decrease in cellulase production on cellulose as observed in T. reesei Rcel1B, while the overexpression of other β-glucosidases did not [ 22 ]. We wondered if the decrease on cellulase production was due to that the promoter cbh1 was too strong, which was considered as the strongest promoter in T. reesei on cellulose [ 40 , 41 ].…”
Section: Resultssupporting
confidence: 92%
“…To investigate its cellular distribution, the C terminus of CEL1B were fused with red fluorescent protein (DsRed) as reported previously (Additional file 1 : Fig. S2) [ 22 ]. Among the three cel1b -overexpressing strains cultivated in TMM + 2% cellulose, the cellular distribution of CEL1B-DsRed could only be observed in strain OEcel1B during 7 days’ fermentation process by confocal laser scanning microscopy (CLSM) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(Hemi)cellulase activity assay, confocal imaging, spore counting, RNA-seq analysis, and RT-PCR were performed as described in our previous research [ 41 , 65 ]. T. reesei RUT-C30 cultured for 24 h with or without 2.92 g/L glutamine were utilized for RNA-seq.…”
Section: Methodsmentioning
confidence: 99%